2015
DOI: 10.1007/s11199-015-0539-0
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Gender Ideology and Gendered Behavior as Predictors of Children’s Gender-Role Attitudes: A Longitudinal Exploration

Abstract: The current study utilized longitudinal, self-report data from a sample of 109 dual-earner, working-class couples and their 6-year-old children living in the northeastern United States. Research questions addressed the roles of parents’ gender ideology and gendered behaviors in predicting children’s development of gender-role attitudes. It was hypothesized that parents' behavior would be more influential than their ideology in the development of their children's attitudes about gender roles. Parents responded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 49 publications
(72 reference statements)
5
101
1
4
Order By: Relevance
“…Although research shows that parents’ behaviors do not always accurately reflect their attitudes (Halpern and Perry-Jenkins 2015; Perry-Jenkins and Crouter 1990), it is well known that parents’ gender-related attitudes are related to children’s gender-related cognitions (see meta-analyses by Degner and Dalege 2013 and Tenenbaum and Leaper 2002). Despite parents’ important role in shaping their children’s toy preferences and playing behavior, there is little research on the relationship between different aspects of parents’ attitudes and behaviors regarding toys and gender, namely their judgements about the desirability of different toys for their children, their gender-typing of toys, and their gender role attitudes (i.e.…”
Section: Parental Influence On Children’s Toy Preferencesmentioning
confidence: 99%
“…Although research shows that parents’ behaviors do not always accurately reflect their attitudes (Halpern and Perry-Jenkins 2015; Perry-Jenkins and Crouter 1990), it is well known that parents’ gender-related attitudes are related to children’s gender-related cognitions (see meta-analyses by Degner and Dalege 2013 and Tenenbaum and Leaper 2002). Despite parents’ important role in shaping their children’s toy preferences and playing behavior, there is little research on the relationship between different aspects of parents’ attitudes and behaviors regarding toys and gender, namely their judgements about the desirability of different toys for their children, their gender-typing of toys, and their gender role attitudes (i.e.…”
Section: Parental Influence On Children’s Toy Preferencesmentioning
confidence: 99%
“…This finding held up across family types, suggesting the possibility that, as they grow older, boys face stronger – and increasingly intense – pressure to conform to gender norms, regardless of family structure. Some prior work has assessed gender development in a variety of ways, examining appearance (Halim et al, 2013), play (Halim et al, 2013), attitudes (Halpern & Perry-Jenkins, 2015), and career aspirations (Williams, Radin, & Allegro, 1992). This work has found that patterns of stability and change may vary by domain (Halim et al, 2013), suggesting that a multidimensional measure of gender-typed behavior (e.g., that assesses play, attitudes, and peer group preferences) may have detected changes in girls’ gender-typed behavior as well.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining three articles in this issue report on studies using quantitative approaches to answer questions regarding gender and families considering a variety of individual and social variables (Henderson et al 2016), across different countries (Treas and Tai 2016), and across time periods (Halpern and Perry-Jenkins 2016). A methodological highlight of the quantitative studies included in Part 2 are the characteristics of the datasets used.…”
Section: Methodological Pluralismmentioning
confidence: 99%
“…Here the reader can find a test of classical gender structuration theory (Treas and Tai 2016), a feminist perspective on gender development in childhood (Halpern and Perry-Jenkins 2016), a feminist sociological lens (Henderson et al 2016), and a feminist social constructionist perspective (Swenson and Zvonkovic 2016). The reader can also find contemporary feminist theories influenced by globalization (Fulu and Miedema 2016).…”
Section: Substantive and Theoretical Pluralismmentioning
confidence: 99%
See 1 more Smart Citation